Kinerja Koperasi PRIMKOPPOL Resor Gunung Kidul - Inaryu Melly Triyani Widodo; Bambang Sugeng Dwiyanto (Universitas Proklamasi 45 Yogyakarta, 2016)
Since 2006 the government of the Republic of Indonesia has awarded to cooperatives achievement. This study is a description of which is an analysis by taking a cooperative object